Cytotoxic Effect of Tilapia Hepcidin TH1-5 on Human Breast Cancer Cell Line (MCF7) - Khamsah Suryati, Mohd; A Dharmaraj, Saravanan; Mohammed Al-Kassim, Hassan; Wan Atirah, Azemin (2015)
Tilapia hepcidin (TH1-5) is a cysteine-rich antimicrobial peptide originally isolated from the freshwater fish Oreochromis mossambicus. A synthesized form of the peptide has been reported to exhibit cytotoxic activity against few human cancerous cell lines. Till date, no studies document the activity of this peptide on human breast cancer cell line (MCF7). This study investigates the potential cytotoxicity of the compound against human breast cancer cell line and normal mouse embryonic fibroblast cell line (NIH/3T3) by using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Tilapia hepcidin TH1-5 showed cytotoxic activity against MCF7 with an IC50 of 20 µg/mL but no significant effect against NIH/3T3. Morphological changes by acridine orange and propidium iodide (AO/PI) double staining were also studied to determine the apoptotic evidences. This outcome indicates hepcidin TH1-5 to be a promising cytotoxic peptide that may warrant further studies as a potential anticancer agent.